Implementasi Sikap Jujur untuk Meningkatkan Perilaku Sosial Siswa Prespektif Akhlak Tasawuf di Sekolah Dasar - Khofifah Indar Lutfiani; Siti Khoirun Nisa’; Septya Relan Alvia Nanda Baisroh; Muhammad Romadhon Habibullah (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2025)
This article discusses the implementation of an honest attitude to improve student behavior in elementary schools from a Sufism moral perspective. The method used is a literature review, in which the author searches for books or journals that are relevant to the topic being discussed. In Sufism, honesty reflects integrity and responsibility. Teachers as role models and collaboration with parents play a very important role in this process. Steps that can be taken include setting an example, motivating students to prioritize honesty, and integrating the value of honesty in daily activities. Challenges such as social influences and academic pressure can be overcome by strengthening the role of teachers and collaboration with parents. With an honest attitude, you can establish harmonious social relations. This approach is in line with Sufism teachings which emphasize honesty in life Keywords: Sufism Morals, Social Behavior, Honest Attitude.